The establishment of an international AI agency: an applied solution to global AI governance. - Robinson, Mark (International Affairs, 2025)
Achieving sustainable, inclusive, fair and binding international regulation in the field of artificial intelligence (AI) is one of the most critical questions of our time. Numerous national, regional and sector-specific initiatives have emerged, and more are being added as governments address AI-related challenges. New bodies aim to establish authority, attract top talent and create legitimacy through quality output and alliances. While many have had a positive impact, this policy paper argues that effective operation requires the establishment under the auspices of the United Nations of an international artificial intelligence agency (IAIA). Despite facing funding issues, the UN's unparalleled convening power is fundamental in guiding the AI governance debate. Only an IAIA can legitimately oversee a global AI governance framework involving all major powers. It must also engage directly with global big tech corporations to ensure credibility and efficacy. While support from global South governments is vital, this paper focuses on collaboration between major political leaders and big tech corporations. While they are not perfect, the IAEA's governance structures provide a ready framework to integrate big tech's influence with member states' reclaimed authority. The paper proposes a bold strategy: a new Grand Bargain for global AI collaboration, with concurrent national and global efforts combining to address diverse issues. Delaying action pending ideal geopolitical conditions risks indefinite inaction. The paper calls for immediate negotiations between the United States and China to establish an 'early IAIA' by 2028, preventing reactive measures following an unforeseen crisis. The paper supports the UN High-Level Advisory Body on AI by defining IAIA success and identifying key groups and motivations for its realization. Establishing the IAIA will require drive and leadership, with the UN secretary-general's Envoy on Technology guiding implementation to complement the Global Digital Compact.